Phenotypic segregation of Aedes aegypti for immune antibacterial activity and resistance to filariae - Ham, P; Yang, H; Nolan, G (the Royal Society, 1996)
We report the phenotypic selection of two lines of Aedes aegypti, from a filariae susceptible parental stock (Refm). This selection was based upon the level of inducible anti-gram negative Escherichia coli activity within the haemolymph following E. coli infection. These lines, denoted `high' and `low', demonstrated significant differences in anti-E. coli responses throughout. However no difference was observed in the anti-gram positive Micrococcus luteus response following E. coli challenge. F$_{4}$, F$_{6}$ and F$_{9}$ mosquitoes were experimentally infected with Brugia pahangi microfilariae. Reductions of between 53 and 82% in the mean number of larvae completing development in the `high' compared with the `low' responding line were observed. Corresponding reductions of between 30 and 50% in the mosquito infection rates also occurred between these lines. These reductions were significant for trials on the F$_{6}$ and F$_{9}$ generations. We have therefore selected for Ae. aegypti possessing significant refractoriness to filaria infection. Importantly, this `high' line has not been exposed to selection pressure using filariae development as a phenotypic selective marker.